Gram-Negative Challenges: Assessing the Decline in Carbapenem Sensitivity Among Klebsiella Pneumoniae Isolates - Rasool Chaloob Hulyal (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Antimicrobial resistance represents a critical global health challenge, particularly among Gram-negative pathogens such as Klebsiella pneumoniae. Specific Background: Carbapenems have served as last-resort therapies for multidrug-resistant infections; however, increasing resistance among K. pneumoniae threatens their clinical utility. Knowledge Gap: Longitudinal epidemiological evidence describing temporal susceptibility trends and associated clinical factors remains underexplored. Aims: This study evaluates temporal changes in carbapenem susceptibility among K. pneumoniae clinical isolates using cumulative antibiogram surveillance. Results: A retrospective analysis of 512 isolates (July 2024–September 2025) demonstrated a marked decline in susceptibility to imipenem (92% to 78%) and meropenem (93% to 82%), with significant reductions between early and late periods (p < 0.05; p < 0.01). Resistance rates increased alongside higher prevalence of carbapenemase-producing strains and MDR/XDR phenotypes. Epidemiological patterns shifted from mixed community–hospital distribution to predominantly nosocomial transmission, particularly in intensive care units, with associations to mechanical ventilation, prolonged hospitalization, invasive devices, and prior broad-spectrum antibiotic exposure. Temporal clustering indicated outbreak-like dynamics in critical care settings. Novelty: This study provides longitudinal antibiogram-based evidence linking declining carbapenem susceptibility with ICU-centered transmission and resistance clustering. Implications: Findings underscore the need for strengthened antimicrobial stewardship, continuous surveillance, and targeted infection control strategies to mitigate hospital-driven dissemination of resistant K. pneumoniae. Highlights:• Progressive reduction in carbapenem sensitivity observed over 15 months• Resistance patterns concentrated within critical care environments• Transmission dynamics shifted toward hospital-dominated infection sources Keywords: Klebsiella Pneumoniae, Antimicrobial Resistance, Carbapenem Resistance, Nosocomial Transmission, Antibiogram Surveillance